Effect of Mg addition on the physical properties of aluminum nitride - Anggraini, Sri Ayu; Uehara, Masato; Yamada, Hiroshi; Akiyama, Morito (Materials letters, 2018)
•c-Axis oriented AlxMg1-xN thin films were deposited on Si (100) using rf sputtering.•Low Mg doping to AlN enhanced the piezoelectric response up to 7.4 pC/N.•Low Mg addition into AlN could increase the stiffness of the thin film. We are reporting the effect of magnesium (Mg) addition into aluminum nitride (AlN) on piezoelectric and mechanical properties. Addition of 2.5 at.% Mg was found to slightly enhance both the piezoelectric constant (d33) (up to 7.4 pC/N) and the relative permittivity (up to 12). Young’s modulus and hardness were decreased when 2.5 at.% Mg was added into AlN and were slightly increased for sample with 5 at.% Mg addition. The dielectric loss was less than 10−2 for samples with Mg addition lower than 8 at.%. However, higher Mg addition (>8 at.%) led to a lower d33, higher relativity permittivity while decreasing Young’s modulus and hardness.